Exportaciones de productos tradicionales en tiempos covid-19: caso Ecuador periodo 2020 - 2021. - Vasquez Armijos, Emily Nathaly; Gonzalez Erazo, Jhostyn Josue (Universidad Técnica de Machala, 2022)
The world is currently experiencing the Covid -19 pandemic and whose consequences, as has been shown, not only affect human health, but also end up influencing the social and economic sphere of all countries. It is important to consider that when dealing with the economic and social effects that were generated by the COVID-19 pandemic, carrying out the analysis of the processes that are carried out in international trade, it is necessary to consider that its different dimensions must also be analyzed. from a national, regional and international perspective. The objective of the research is: To evaluate the impact of COVID-19 on exports of traditional products during the 2010-2020 period that allows the design of public policies that strengthen this sector of the economy.The methodology used is a descriptive research with a documentary and analytical method. Therefore, sources available on the network were reviewed, whose content is current, published in science journals, available in Google Scholar, as adjusted to the purpose of the topic, with timely and relevant content from the scientific point of view. The results of the research show that the export structure of traditional and non-traditional products, in their participation, has varied since the beginning of the millennium. For the increase in exports, the alternative solution is related to productive diversification, which is the process through which it is decided to add new products to its current portfolio, emphasizing the international market.
Actualmente el mundo se encuentra viviendo la pandemia del Covid -19 y cuyas consecuencias, como ha quedado evidenciado, no sólo afectan a la salud humana, sino que también termina influenciando en el ámbito social y económico de todos los países. Es importante considerar que al tratarse de los efectos económicos y sociales que se generaron por la pandemia del COVID – 19 el realizar el análisis de los procesos que se llevan a cabo en el comercio internacional siendo necesario considerar que se deben también analizar sus distintas dimensiones, desde un enfoque nacional, regional e internacional. El objetivo de la investigación es: Evaluar el impacto del COVID-19 sobre las exportaciones de productos tradicionales durante el periodo 2010-2020 que permita el diseño de políticas públicas que fortalezcan a este sector de la economía. La metodología empleada es una investigación descriptiva de método documental y analítico. Por lo que se revisaron fuentes disponibles en la red, cuyo contenido sea actual, publicados en revistas de ciencia, disponibles en Google Académico, lo más ajustadas al propósito del tema, con contenido oportuno y relevante desde el punto de vista científico. Los resultados de la investigación evidencian que la estructura de exportación de los productos tradicionales y no tradicionales, en su participación, ha variado desde inicios del milenio. Para el incremento de las exportaciones la alternativa de solución se relaciona con la diversificación productiva, el cual es el proceso a través se decide añadir nuevos productos a su actual cartera, poniendo énfasis en el mercado internacional.
Keywords: SECTOR EXTERNO; PRODUCTOS TRADICIONALES; COVID-19; MERCADOS INTERNACIONALES